Implementation of the Value of Justice in Pancasila can Improve the Quality of Life in Society, Nation and State - Dian Andriani Ratna Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Indonesian nation aspires to realize a just and prosperous national life for that it is necessary to understand and implement the values of Pancasila. The current swift current of globalization has eroded the understanding of future generations about the values contained in Pancasila. This problem of understanding has resulted in the abandonment and oblivion of Pancasila. National identity must be rebuilt by actualizing the values of Pancasila so that it can be a guide in responding to various challenges now and in the future. If we do not succeed in re-actualizing the values of Pancasila, then Pancasila will be alienated from the life of the Indonesian nation. The national values contained in Pancasila are religious values, kinship, harmony, democracy and justice. This paper will discuss the implementation of the value of justice in improving the quality of life in society, nation and the state.